Effect on Feeding Thymolina Powder in The Carcass Characteristics and Morphology of Small Intestine of Ross 308 Broiler Chickens (PENGIMBUHAN BUBUK THYMOLINA DALAM RANSUM MEMPERBAIKI PERFORMANS DAN MORFOLOGI USUS HALUS AYAM PEDAGING) - Hosseini, Seyyedmousa; Chamani, Mohammad; Seidavi, Alireza; Sadeghi, Ali Asghar; Ansari-Pirsaraei, Zarbakht (Jurnal Veteriner; Vol 17 No 4 (2016), 2017)
This study was performed to elucidate the association effect on feeding thymolina powder in thecarcass characteristics and morphology of small intestine of Ross 308 broiler chickens. In the presentexperiment, 320 one day old Ross 308 broiler chickens were used by using completely randomized designwith 4 treatments, 4 replicates, in which each replicate contained 20 broiler chickens. Experimentaltreatments groups were: control, 0.5, 1, and 2% of Thymolina powder in chickens’ diet. Thymolina® is ananti-bacterial powder drug which is made by composing 4 medicinal plants. A significant difference observedamong treatments in each parameter of the intestinal morphology (villus height, villus width, crypt depthand epithelial thickness. The number of goblet cells were not affected. Results of this findings indicatedthat using Thymolina® in the diet of broiler chickens causes improvements in carcass characteristics.Therefore, it may improve the performance and creation of the favorable broiler chickens.
Keywords: broiler; morphology; Ross 308; small intestine; thymolina®